Is Epstein-Barr Virus Infection Associated With Thyroid Tumorigenesis?—A Southern China Cohort Study - Yu, Shi-Tong; Ge, Jun-Na; Li, Rui-Chen; Wei, Zhi-Gang; Sun, Bai-Hui; Jiang, Yu-Ming; Luo, Jing-Yi; Liu, Hao; Lei, Shang-Tong (Frontiers in Oncology, 2019)
Background: Epstein-Barr virus (EBV) is associated with many epithelial malignancies. A few reports on the association between EBV and thyroid tumorigenesis have been investigated. However, the conclusion is highly contradictory. We aimed to explore the role of EBV in thyroid nodule development and its clinical significance in a cohort from southern China. Method: We conducted a retrospective data abstraction study of patients who underwent thyroidectomy between December 2017 and June 2018. We retrospectively analyzed the clinicopathological parameters and EBV infection status (serological antibodies and in situ hybridization). Result: The cohort comprised 384 patients with newly diagnosed thyroid diseases, including 261 papillary thyroid carcinomas, 87 nodular goiters, 21 follicular adenomas, 12 follicular thyroid carcinomas, and 3 medullary thyroid carcinomas. Forty-two (10.9%) patients were identified as being serological antibody positive. However, there was no association between the clinicopathological parameters and serological antibody positivity. Additionally, none of the patients showed EBER expression in thyroid normal/cancer cell nuclei in in situ hybridization. Conclusion: In this study, no correlation between EBV and thyroid diseases was found in a cohort from southern China.